Family health nursing care: weaknesses and strengths in the Unified Health System - Simone Santana da Silva; Marluce Maria Araújo Assis (SciELO, 2015)
OBJECTIVETo analyze the weaknesses and strengths of nursing care in the Family Health Strategy and its interfaces with the Unified Health System network.METHODA qualitative study performed by means of semi-structured interviews and systematic observations, with the participation of a nursing team of 15 people from October of 2012 to January of 2013.RESULTSStrengths that were emphasized: the nurse's versatility in conducting users within the unit and the health system, therefore directly acting upon access to these services. The nurse is the main subject that participates in the care processes for the person, family and social groups. Weaknesses that were highlighted: fragile embracement and low resolution of users' and families' problems.CONCLUSIONThe nursing care process in health units still lacks collective articulation, involvement of the team, and decentralization of the decisions.